209k views
2 votes
Please help with this question, thank you!!​

Please help with this question, thank you!!​-example-1

2 Answers

4 votes

Answer:


-√(2)

Explanation:

Note that:


a^2-2ab+b^2=(a-b)^2 = 4ab \\ \\ a^2 + 2ab+b^2 = (a+b)^2 = 8ab \\ \\ \implies (a+b)/(a-b)=(√(8ab))/(-√(4ab))=-√(2)

User MisterXero
by
5.9k points
4 votes

Answer:


\sf (a+b)/(a-b)= -√(2)

Explanation:


\sf a^2 + b^2 = 6ab \qquad where\:\:0 < a < b

Basic formula:


\sf (a + b)^2 = a^2 +b^2 +2ab


\sf (a - b)^2 = a^2 + b^2 -2ab

solve for a + b


\sf \rightarrow a^2 + b^2 = 6ab


\sf \rightarrow (a+b)^2-2ab = 6ab


\sf \rightarrow (a+b)^2 = 6ab+2ab


\sf \rightarrow (a+b)^2 = 8ab


\sf \rightarrow a+b = \pm √(8ab)

solve for a - b


\sf \rightarrow a^2 + b^2 = 6ab


\sf \rightarrow (a-b)^2 + 2ab = 6ab


\sf \rightarrow (a-b)^2 = 6ab-2ab


\sf \rightarrow (a-b)^2 = 4ab


\sf \rightarrow a-b = \pm √(4ab)

Now solve for (a + b)/(a - b)


\sf \rightarrow (a+b)/(a-b)= (\pm√(8ab) )/(\pm√(4ab) )


\sf \rightarrow (a+b)/(a-b)= \pm \sqrt(8ab )/(4ab)


\sf \rightarrow (a+b)/(a-b)= \pm √(2)

As, the value of b is greater than the value of a and both the values a and b are greater than 0. It turns the value of expression negative as the denominator will be always evaluated to negative integer and the numerator value always > 0. So, the answer will be negative, -√2.


\sf \rightarrow (a+b)/(a-b)= - √(2)

User Nickgroenke
by
6.8k points